Literal Reading in Academic English Texts among EFL Undergraduate Thesis Writers: A Mixed-Method Exploration - Herman Resyadi; Ferawaty Syam; Uswatunnisa (Eduvelop: Journal of English Education and Development, 2026)
This research investigated how EFL undergraduate thesis writers engage in and perceive literal reading when working with academic English texts. An explanatory sequential mixed-method design was employed, involving questionnaire data from 38 undergraduate thesis writers and follow-up interviews with seven purposively selected participants. Quantitative data were analyzed descriptively, while qualitative data were examined using thematic analysis. The findings indicate that students actively engage in literal reading strategies such as scanning, highlighting, and translation and report strong confidence in locating explicit information, identifying main ideas, and recognizing cohesive ties in academic texts. However, interview data revealed that their reading performance is frequently constrained by limited vocabulary and the structural complexity of academic texts, leading students to rely on compensatory rather than fluent reading practices. Overall, the findings suggest that literal reading remains a foundational yet insufficiently developed component of academic literacy among EFL undergraduate thesis writers. This research contributes to the literature by highlighting the gap between students’ perceived literal reading competence and the actual lexical and structural demands of academic English, underscoring the need for explicit instructional support in vocabulary development and literal reading strategies in higher education contexts.